PENGARUH KOMPETENSI TERHADAP KINERJA PEGAWAI DINAS PENGELOLAAN KEUANGAN DAN ASET KABUPATEN ROKAN HULU - -, Yenni (Jurnal Mahasiswa Prodi SI Manajemen, 2013)
Interest [is] ability to run aktivits in function or work as according to standard expected by company or organisation. Interest also represent a[n ability to execute or [do/conduct] a[n job or task based on of knowledge and skill [is] and also supported by [job/activity] attitude claimed by work.This research aim to to know Interest officer, Officer performance and influence of interest to officer performance [at] On duty Management of Finance and Asset Sub-Province of Rokan Pate;Upstream.This Research [is] [done/conducted] [At] On duty Management of Finance and Asset [in] Government Of Sub-Province of Rokan Pate;Upstream. its Technique Intake [of] him by random sampling that is at random [at] officer On duty monetary Management and Asset Sub-Province of Rokan Pate;Upstream, sampel which [is] used in this research [is] counted 53 officer people.Data type which [is] needed in this research [is] primary data and data of sekunder. Technique data collecting use observation, interview, and documentation of kuistioner. Analysis the used [is] analysis of regresi linear modestly.Influence of Interest to officer performance [at] On duty Management of Finance and Asset Sub-Province of Rokan Pate;Upstream in the reality there are [relation/link] which are positive, where change of value [at] interest category followed also by change of value [at] performance category of pagawai. Result of Research indicate that interest have influence which [is] dignifikan to officer performance, but its storey;level [it] small relative. This result indicate that each;every increase of Interest variable equal to 1% causing kanaikan [at] Officer performance equal to 20